The impact of secondary forest restoration on multiple ecosystem services and their trade-offs. (September 2019) - Zeng, Yelin; Gou, Mengmeng; Ouyang, Shuai; Chen, Liang; Fang, Xi; Zhao, Lijuan; Li, Jiaxiang; Peng, Changhui; Xiang, Wenhua
Graphical abstract: Highlights: Late stage forest supplied higher overall and more evenly distributed ES benefits. Magnitudes of trade-offs between paired ESs changed with restoration stages. The beneficiary in several paired trade-offs changed along the restoration gradient. Tree functional groups are important to ES trade-offs and ecosystem management. Abstract: Secondary forests have received more attention in recent decades because their total area is increasing and the greater recognition of ecological and economical benefits provided by forest ecosystems. Therefore, the Chinese government has given high priority to implementing its Natural Forest Program that includes the restoration of degraded secondary forests. Hence, how ecosystem services (ESs) and their trade-offs are altered during the restoration process of secondary forests merits research. Here, we selected five key ecological indicators of forests, namely plant diversity and four ESs—air quality regulation, maintenance of soil fertility, global climate regulation, and timber provisioning—to examine the trends and patterns in the variation of multiple indicators and their trade-offs during forest restoration. Furthermore, secondary forests in subtropical China are characterized by a diverse tree species community that transitions from conifers in the early stage of restoration, to deciduous broadleaf and evergreen broadleaf species in its mid and late stages; this provides an excellent opportunity to investigate the influences of different tree functional groups on ESs and the trade-offs among them. Our results showed that late-forest had a greater capacity to supply higher and more evenly distributed benefits of ESs than did early or mid-stage restored forests. We also found that the magnitude of trade-offs between paired ESs changed with the stage of restoration. Furthermore, the variation of the beneficiary in critical trade-offs corresponded to the patterns of change in benefits of specific ESs. Trade-offs between plant diversity and other ESs were significantly influenced by tree functional group, in that the deciduous broadleaved species had significant positive effects whereas the conifer and evergreen broadleaved species had negative effects. We conclude that accurate prediction and management of ESs in restoration forests should explicitly account for tree functional groups, in addition to the effects from combined trade-offs among multiple ESs.